Chemical characteristics of kelulut honey (Trigona sp.) in Bangka Tengah District, Indonesia. Issue 1 (March 2021) - Evahelda,; Setiawan, I; Aini, S N; Afriani, Z L
Abstract: Honey is a natural liquid which generally has a sweet taste produced by honey bees (Apis sp.) from floral nectar or other parts of plants (extrafloral). Kelulut honey is the honey produced by kelulut bees (Trigon sp). The kelulut bee is a member of the Meliponidae family (Stingless bee) and has a smaller body size compared to Apis bees, making it safe for cultivation. The honey quality cannot be uniformed every time it is harvested. This is because the physical and chemical quality characteristics of honey are very dependent on external and internal factors. External factors that influence it are the source of nectar, season, soil or geographic conditions, processing, and storage conditions. The internal factor that influences it is the type of bee. This study aimed to analyze the chemical characteristics of Bangka kelulut honey based on the Indonesian National Standard (SNI) 3545: 2013. The honey sample used was fresh kelulut honey without processing from the Karomah Forest Farmer Group in Lubuk Lingkuk Village, Lubuk Besar District, Central Bangka Regency. The results showed that the chemical quality characteristics of Bangka kelulut honey have not passed the standards set by the Indonesian National Standard (SNI) 3545: 2013, especially on water content, reducing sugar content and acidity, respectively 28.7%, 59.3%, and 74.6 ml NaOH/kg. Kelulut honey also has vitamin C of 24.1 mg/kg.